Pengaruh Fear of Missing Out (Fomo), Self-Control, dan Digital Financial Literacy terhadap Perilaku Keuangan Mahasiswa Feb Universitas Negeri Jakarta - Aini Shabrina Nurinsani; Erika Takidah; Susi Indriani (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This inquiry intends to evaluate and explicate both the isolated and concurrent impacts of Fear of Missing Out (FoMO), Self-Control, and Digital Financial Literacy regarding Financial Management Behavior. Utilizing a quantitative framework alongside a causal associative survey methodology, this exploration was executed within the Faculty of Economics and Business at Universitas Negeri Jakarta. The target population encompassed 626 active undergraduate students from the 2022 stream, from which a representative group of 244 participants was determined via proportionate random sampling utilizing Slovin’s formulation. Primary insights were gathered through online structured questionnaires structured around a five-point Likert scale. Computational assessment was executed via IBM SPSS version 31, which included descriptive analytics, residual normality verification through the One-Sample Kolmogorov-Smirnov test, and multiple linear regression modeling. The statistical outcomes reveal that Fear of Missing Out yields a significant adverse effect on students’ financial habits. Conversely, both Self-Control and Digital Financial Literacy demonstrate favorable and significant positive contributions toward financial execution. Collectively, the three independent components substantially determine students’ financial accountability, exhibiting an extensive coefficient of determination. These conclusions indicate that optimizing financial responsibility among young generations demands a comprehensive strategy that bridges technical-cognitive capability with internal psychological stabilization to reduce social anxieties.